Microalgae production in fresh market wastewater and its utilization as a protein substitute in formulated fish feed for oreochromis spp. - Hairuddin, Nur Diyana; A. Talip, Balkis; Neo, Zhi Zing; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel; Muhammad, Norhayati; Abdullah, Norazlin; Mohd Kahar, Ernna Erynna; Abdullah, Shakila (Springer Nature, 2020)
Rapid growing of human population has led to increasing demand of aquaculture production. Oreochromis niloticus or known as tilapia is one of the most globally cultured freshwater ﬁsh due to its great adaptation towards extreme environment. Besides, farming of tilapia not only involves small scales farming for local consumption but also larger scales for international market which contributes to a foreign currency earning. Extensive use of ﬁshmeal as feed for ﬁsh and for other animals indirectly caused an increasing depletion of the natural resource and may consequently cause economic and environmental unstable. Microalgae biomass seems to be a promising feedstock in aquaculture industry. It can be used for many purposes such as live food for ﬁsh larvae and dried microalgae to substitute protein material in ﬁsh feed. The microalgae replacement in ﬁsh feed formulation as protein alternative seem potentially beneﬁcial for long term aqua-business sustainability. The present chapter discussed the potential of microalgae as an alternative nutrition in ﬁsh feed formulations, speciﬁcally Tilapia.